Aspergillus fumigatus-Related Species in Clinical Practice - Lamoth, Frédéric (Frontiers in Microbiology, 2016)
Aspergillus fumigatus is the main etiologic agent of invasive aspergillosis (IA). Other Aspergillus species belonging to the section Fumigati (A. fumigatus complex) may occasionally be the cause of IA. These strains are often misidentified, as they cannot be distinguished from A. fumigatus by conventional morphological analysis and sequencing methods. This lack of recognition may have important consequences as these A. fumigatus-related species often display some level of intrinsic resistance to azoles and other antifungal drugs. A. lentulus, A. udagawae, A. viridinutans and A. thermomutatus (Neosartorya pseudofischeri) have been associated with refractory cases of IA. Microbiologists should be able to suspect the presence of these cryptic species behind a putative A. fumigatus isolate on the basis of some simple characteristics, such as defect in sporulation and/or unusual antifungal susceptibility profile. However, definitive species identification requires specific sequencing analyses of the beta-tubulin or calmodulin genes, which are not available in most laboratories. Multiplex PCR assays or matrix-assisted laser desorption ionization – time-of-flight mass spectrometry (MALDI-TOF MS) gave promising results for rapid and accurate distinction between A. fumigatus and other Aspergillus spp. of the section Fumigati in clinical practice. Improved diagnostic procedures and antifungal susceptibility testing may be helpful for the early detection and management of these particular IA cases.